2012
DOI: 10.1017/s1461145712000685
|View full text |Cite
|
Sign up to set email alerts
|

A physiological role for the dopamine D5 receptor as a regulator of BDNF and Akt signalling in rodent prefrontal cortex

Abstract: The dopamine D5 receptor (D5R) exhibits a wide distribution in prefrontal cortex (PFC) but its role in this region has not yet been elucidated. In the present study we identified a novel physiological function for the D5R as a regulator of BDNF and Akt signalling in PFC. Specifically, acute activation of the D5R by the dopamine agonist SKF 83959 enhanced BDNF expression and signalling through its receptor, TrkB, in rats and in mice gene-deleted for the D1 receptor but not the D5R. These changes were concomitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 25 publications
3
64
0
Order By: Relevance
“…As a physiologically relevant fraction of MSNs within the NAc and globus pallidus express the D1-D2 receptor heteromer (Perreault et al, 2010), together these findings strongly implicate this receptor complex as being significant to dopamine transmission and should be investigated as a therapeutic target for schizophrenia. Further support for a potential role for the D1-D2 heteromer in schizophrenia comes from a recent finding demonstrating that activation of the D1-D2 receptor heteromer could inactivate glycogen synthase kinase-3b (GSK-3b) in rodent prefrontal cortex (PFC) (Perreault et al, 2013) (Figure 1). In schizophrenia, cortical GSK-3b activation is upregulated (Emamian et al, 2004) and has been implicated as contributing to cognitive dysfunction in the disorder Karam et al, 2010).…”
Section: The Dopamine D1-d2 Receptor Heteromermentioning
confidence: 99%
“…As a physiologically relevant fraction of MSNs within the NAc and globus pallidus express the D1-D2 receptor heteromer (Perreault et al, 2010), together these findings strongly implicate this receptor complex as being significant to dopamine transmission and should be investigated as a therapeutic target for schizophrenia. Further support for a potential role for the D1-D2 heteromer in schizophrenia comes from a recent finding demonstrating that activation of the D1-D2 receptor heteromer could inactivate glycogen synthase kinase-3b (GSK-3b) in rodent prefrontal cortex (PFC) (Perreault et al, 2013) (Figure 1). In schizophrenia, cortical GSK-3b activation is upregulated (Emamian et al, 2004) and has been implicated as contributing to cognitive dysfunction in the disorder Karam et al, 2010).…”
Section: The Dopamine D1-d2 Receptor Heteromermentioning
confidence: 99%
“…12,13 Their effects on dopaminergic neuronal function in particular may be a critical path for drug addiction because the dopamine (DA) system is a key component of the brain circuitry of motivation and reward. [14][15][16] Preclinical investigations have demonstrated that cocaine administration can increase the levels of BDNF in rodents. 17,18 Furthermore, recent studies have shown a significant increase in BDNF levels over the first days of cocaine abstinence in both preclinical and clinical models, which is most likely due to compensatory mechanisms activated in response to the neurotoxic effects of chronic cocaine exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, phosphorylation by CaMKII is also involved in the functional regulation of the α-amino-3-hydroxyl-5-methyl-4-isoxazole-propionate receptor (AMPAR) [44], thus contributing to AMPAR-induced changes in synaptic plasticity that mediate the development of addiction [44,45,46]. As D 1 -D 2 heteromer activation has been shown to be associated with changes in the expression and/or activation of BDNF [23,25,31,47], GSK-3 [48] and AMPARs [26] in vivo, the present review will discuss the potential contribution of these signaling cascades in addiction, thus highlighting their possible contribution to adolescent addiction susceptibility and a possible role for the D 1 -D 2 heteromer in regulating addiction processes.…”
Section: The Dopamine D1-d2 Receptor Heteromermentioning
confidence: 99%
“…Phosphorylation of GSK-3β has been shown to occur by numerous mechanisms including direct phosphorylation by protein kinase C [85,86], CaMKII [38] and Akt [87], as well as indirectly via β-arrestin1 [88,89], cyclin-dependent kinase 5 [90], and following activation of tyrosine receptor kinases such as the insulin receptor [87,91] or the BDNF receptor, TrkB [92,93]. Importantly, in recent years dopamine has been shown to be a key mediator in the regulation of GSK-3β activity [48,94,95]. In two distinguished studies by Beaulieu et al [94,95] dopamine was identified to increase the activation of striatal GSK-3α and GSK-3β via a mechanism involving β-arrestin2 signaling, mediated by the D 2 R, and a process that was induced in mice following AMPH administration.…”
Section: Glycogen Synthase Kinasementioning
confidence: 99%
See 1 more Smart Citation